An in vitro culture system for long-term expansion of epithelial and mesenchymal salivary gland cells: Role of TGF- β 1 in salivary gland epithelial and mesenchymal differentiation - Janebodin K. (2014)
Despite a pivotal role in salivary gland development, homeostasis, and disease, the role of salivary gland mesenchyme is not well understood. In this study, we used the Col1a1-GFP mouse model to characterize the salivary gland mesenchyme in vitro and in vivo. The Col1a1-GFP transgene was exclusively expressed in the salivary gland mesenchyme. Ex vivo culture of mixed salivary gland cells in DMEM plus serum medium allowed long-term expansion of salivary gland epithelial and mesenchymal cells. The role of TGF- β 1 in salivary gland development and disease is complex. Therefore, we used this in vitro culture system to study the effects of TGF- β 1 on salivary gland cell differentiation. TGF- β 1 induced the expression of collagen, and inhibited the formation of acini-like structures in close proximity to mesenchymal cells, which adapted a fibroblastic phenotype. In contrast, TGF- β R1 inhibition increased acini genes and fibroblast growth factors (Fgf-7 and Fgf-10), decreased collagen and induced formation of larger, mature acini-like structures. Thus, inhibition of TGF- β signaling may be beneficial for salivary gland differentiation; however, due to differential effects of TGF- β 1 in salivary gland epithelial versus mesenchymal cells, selective inhibition is desirable. In conclusion, this mixed salivary gland cell culture system can be used to study epithelial-mesenchymal interactions and the effects of differentiating inducers and inhibitors. © 2013 Kajohnkiart Janebodin et al.